OP97 The burden of hypertension and its associated factors in the gambia: data from a national health examination survey using the world health organisation (who) stepwise approach. (2nd September 2017) - Cham, B; Scholes, S; Fat, L Ng; Groce, N; Mindell, JS
Abstract : Background: Non-communicable diseases are increasing in sub-Saharan Africa (SSA). They are estimated to account for 32% of deaths in The Gambia according to the WHO. Worldwide, prevalence of hypertension is highest in the African region (46%) and a very high proportion is undiagnosed. There is very limited up-to-date information on the burden of diagnosed and undiagnosed hypertension and associated risk factors in The Gambia. This study aims to examine cardiovascular risk factors in in The Gambia adult population, with a particular focus on diagnosed and undiagnosed hypertension. Methods: Data was collected from a random, nationally-representative sample of 4111 participants aged 25–64 years (78% response rate) in 2010 using the WHO STEPwise survey methods. Analysis was restricted to non-pregnant participants with three valid blood pressure (BP) measurements (n=3573). All analysis were weighted and adjusted for complex survey design using STATA14. The mean of the second and third BP measurements was used in the analysis. Hypertension was categorised into measured (SBP ≥140 mmHg and/or DBP ≥90 mmHg) and total (SBP ≥140 mmHg and/or DBP ≥90 mmHg and/or self-reported hypertension). Among people with total hypertension, we also looked at undiagnosed hypertension (proportion of participants with hypertension not aware of their status). Univariate and multivariate regression models were run to identify the most important factors associated with hypertension including sex, age, rural/urban residence, socioeconomic and anthropometric factors. Smoking status and fruit and vegetable intake were additional covariates. Results: One third of adults were hypertensive; this was higher in rural regions (40%, p<0.001). Multivariate analysis revealed increased odds of total hypertension among the overweight/obese and rural residents. Abdominal obesity (OR1.8 [95% CI, 1.2–2.7]), rural residence (3.0 [1.6–5.5]), and age were the most important predictors among men while in women it was generalised obesity (2.4 [1.6–3.7]), rural residence (2.5 [1.4–4.5]), and age. More than three-quarters of hypertensive participants were undiagnosed: this was higher among males (86% vs 71%, p<0.001). Men (3.1 [1.7–5.6]) and participants aged 25–34 years (4.8 [1.4–3.5]) had higher odds of undiagnosed hypertension after adjusting for other factors. However, obesity was protective for undiagnosed hypertension (0.4 [0.2–0.6]). Conclusion: Contrary to what is found in similar studies in SSA, where hypertension is highest in urban areas, we found that rural residence, abdominal obesity among men and generalised obesity among women were the most important predictors of hypertension. Intervention to reduce hypertension could be further targeted towards rural areas. Sensitisation campaigns should promote awareness of the risk factors, especially on the importance of maintaining a healthy weight.